2013
DOI: 10.1002/jssc.201201151
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organic pollutants in coking wastewater by dispersive liquid-liquid microextraction/GC/MS

Abstract: A method based on dispersive liquid-liquid microextraction coupled with GC/MS was developed for quantitative analysis of the major organic pollutants listed in the United States Environmental Protection Agency method 8270 and the 15 European-priority polycyclic aromatic hydrocarbons in coking wastewater. The major parameters such as extraction solvent, dispersive solvent, solution pH, and extraction time were systematically optimized. The optimum extraction conditions were found to be: 15 μL mixture of 2:1 v/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Generally, phenols account for about 80% of the total COD amount in coking wastewater [18,19]. Song et al analyzed coking wastewater from six coking plants [20]. Results showed that the sum of concentration of phenols and anilines was 23.8 ± 3.0 mg L À1 , but the sum of 16 PAHs's concentration was 0.66 ± 0.10 mg L À1 .…”
Section: Introductionmentioning
confidence: 96%
“…Generally, phenols account for about 80% of the total COD amount in coking wastewater [18,19]. Song et al analyzed coking wastewater from six coking plants [20]. Results showed that the sum of concentration of phenols and anilines was 23.8 ± 3.0 mg L À1 , but the sum of 16 PAHs's concentration was 0.66 ± 0.10 mg L À1 .…”
Section: Introductionmentioning
confidence: 96%
“…Coking wastewater (CWW) generated during coke production has garnered wide attention due to its mixture of diverse organic contaminants that are hazardous to ecosystems and human health (Song et al 2013;Zhang et al 2013;Felföldi et al 2010;Zhao et al 2014;Hou et al 2015). CWW is generally treated by biological methods such as conventional activated sludge processes (Vazquez et al 2006;Maranon et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…35 (description of ♂, ♀); Gravely 1931: 261, fig. 16d; Tikader and Biswas 1981: 69, figs 120–121; Gong 1989: 109, figs 1–13; Zhang and Hu 1989: 58, figs 7, 22; Majumder and Tikader 1991: 23, figs 30–35; Biswas and Raychaudhuri 1996: 199, figs 27–33; Song et al 1999: 415, figs 245L–M, 248F–G; Dankittipakul and Singtripop 2008: 37, figs 5–7, 30–33; Dankittipakul et al 2012: 59, figs 25–31; Yin et al 2012: 1095, figs 575a–e.…”
Section: Taxonomymentioning
confidence: 99%